Preferable academic work forms of medical students in the era of digitalization - I. E. Zolin; A. A. Iudin; D. I. Iudin; A. I. Iudin (Цифровая социология)
The article presents the sociological study results on the preferred forms of medical students’ academic work in the era of digitalization. The study was carried out among students of the Volga Research Medical University using an online survey. The study purpose is to identify the attitude of various typological groups of medical students to various forms and methods of scientific and methodological support of the educational process, including the use of digital technologies. The work showed that behind the variety of medical students’ attitudes on the effectiveness of different forms of education, there is a willingness of young people to move away from traditional methods of obtaining professional knowledge and skills, and they clearly have a complex request for new forms of teaching, including using the Internet and electronic resources. The assessment of various forms and teaching methods has noticeable differences depending on the affiliation of students to various faculties. The article analyzes the students’ assessments of the various forms’ effectiveness of education using multidimensional data analysis, which made it possible to identify four types of student attitudes: 1) orientation to online learning; 2) live contact with the teacher; 3) electronic library; 4) work with summaries of educational materials. Each of these types contains its own set of preferred and rejected items